Traces Synchronization in Distributed Networks. (20th July 2009) - Clément, Eric; Dagenais, Michel
Abstract : This article proposes a novel approach to synchronize a posteriori the detailed execution traces from several networked computers. It can be used to debug and investigate complex performance problems in systems where several computers exchange information. When the distributed system is under study, detailed execution traces are generated locally on each system using an efficient and accurate system level tracer, LTTng. When the tracing is finished, the individual traces are collected and analysed together. The messaging events in all the traces are then identified and correlated in order to estimate the time offset over time between each node. The time offset computation imprecision, associated with asymmetric network delays and operating system latency in message sending and receiving, is amortized over a large time interval through a linear least square fit over several messages covering a large time span. The resulting accuracy is such that it is possible to estimate the clock offsets in a distributed system, even with a relatively low volume of messages exchanged, to within the order of a microsecond while having a very low impact on the system execution, which is sufficient to properly order the events traced on the individual computers in the distributed system.